2020
DOI: 10.1038/s41598-020-65297-2
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Forcing Scenarios: Predicting Climate Change through Response Operators in a Coupled General Circulation Model

Abstract: Global climate Models are key tools for predicting the future response of the climate system to a variety of natural and anthropogenic forcings. Here we show how to use statistical mechanics to construct operators able to flexibly predict climate change. We perform our study using a fully coupled model-MPI-ESM v.1.2-and for the first time we prove the effectiveness of response theory in predicting future climate response to co 2 increase on a vast range of temporal scales, from inter-annual to centennial, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 86 publications
0
53
0
Order By: Relevance
“…However, the analytical set of solutions for the temperature response to a step change in forcing is the same in either case -a superposition of decaying exponential modes with different timescales varying between a few years and a few centuries (Proistosescu and Huybers, 2017). It has been shown that the implications of these additional degrees of freedom and ambiguity over contributions from different timescales of response might imply that EffCS may not be strongly constrained by temperature change over the last century (Proistosescu and Huybers, 2017;Andrews et al, 2018), and that the long-term equilibrium (LTE) sensitivity may be greater than that implied by EffCS (Otto et al, 2013;Lewis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the analytical set of solutions for the temperature response to a step change in forcing is the same in either case -a superposition of decaying exponential modes with different timescales varying between a few years and a few centuries (Proistosescu and Huybers, 2017). It has been shown that the implications of these additional degrees of freedom and ambiguity over contributions from different timescales of response might imply that EffCS may not be strongly constrained by temperature change over the last century (Proistosescu and Huybers, 2017;Andrews et al, 2018), and that the long-term equilibrium (LTE) sensitivity may be greater than that implied by EffCS (Otto et al, 2013;Lewis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In all of the mentioned examples, the generality of the RFI method allows for the derivation of the appropriate linear response functions for any model by taking only data from an arbitrary perturbation experiment and a control experiment. Such generality opens the possibility of combining the linear response framework, which has been gaining increasing attention due its wide applicability in climate science (e.g., Lucarini, 2009;Lucarini and Sarno, 2011;Lucarini et al, 2014;Ragone et al, 2016;Lucarini et al, 2017;Aengenheyster et al, 2018;Ghil and Lucarini, 2020;Lembo et al, 2020;Bódai et al, 2020), with model intercomparison studies, hopefully leading to a deeper understanding of critical differences encountered across models.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is called the Gallavotti-Cohen hypothesis (Gallavotti and Cohen, 1995a, b). With this assumption, response theory has been successfully used in various weather and climate-related problems (Demaeyer and Vannitsem, 2018;Vissio and Lucarini, 2018;Lembo et al, 2019;Bódai et al, 2020). Indeed, the systems used to produce weather forecasts are typically not uniformly hyperbolic, but thanks to the aforementioned hypothesis, one can still use what will follow and compare with the results obtained with experiments.…”
Section: Response Theorymentioning
confidence: 99%